Ways of optimizing medical services for children at educational institutions under the Health Care system reform in Ukraine. - I. M. Khomenko; O. P. Ivakhno; N. M. Zakharova (Medičnì Perspektivi)
Aim – scientific substantiation of the ways to optimize preventive childhood medicine under the health care system reform in Ukraine. The medical, sanitary and epidemiological conditions of children’s stay were studied at 147 schools in five oblasts of Ukraine and the city of Kyiv. The following methods were used: system analysis, analytical, mathematical and statistical, bibliosemantic, modeling and expert assessments. The results of an expert assessment (224 specialists) on the optimization of medical services for schoolchildren were analyzed. The main risk factors for schoolchildren staying at educational institutions were identified: daily routine failure, non-compliance with the hygiene requirements for the premises where the educational process is carried out, as well as failure in food and water quality and safety. The levels of medical observation provision were analyzed. There were suggested two ways of maintaining the role of medical personnel in preserving and enhancing the health of schoolchildren: involving doctors of primary care centers of the Ministry of Health of Ukraine and creating an autonomous medical service in the institutions of the Ministry of Education and Science of Ukraine in accordance with the current licensing requirements. The issues of prevention and promotion of children's health, including schoolchildren, are one of the key aspects of the training of medical personnel at all stages. Such programs need to be modernized on the basis of a competency approach, taking into account the current needs of the health care system and the best international experience in resolving these issues.